Advances in Solar Energy Technology Volume 1: Collection and Storage Systems - Garg, H. P. (Springer Netherlands, 1987)
The main objective of writing the three volume 'Advances in Solar Energy Technology' is to consolidate all the relevant latest information available in the field of solar energy (applied and theoretical in nature) and to as sist both the students ( i. e. undergraduate, postgraduate, research scholars etc.) and the professionals (i.e. consulting, design and contracting firms). I have discussed each and every topic in depth rather than a cursory overview. All the material required on a particular topic is included in the chapter and I have wherever possible given useful relationships in equation, graphical and tabular form. It is hoped that this completed Solar Energy Technol ogy will serve the best source material in this field. The first chapter deals with the evacuated tubular col lecors suitable to operate at a temperature of about 150°C with a daily energy collector efficiency in excess of 40 per cent. These collectors thus would be useful for efficient operation of Solar Airconditioning System, Power Generation and Process Heat System. Various advanced features like vacuum insulation, selective black coating, anti-reflective coating, heat pipe, cusp reflector, etc., used in designing this advanced type of collector are discussed separately in this chapter. Transient mathematical model for its perfor mance prediction and different designs of evacuated tubular collectors commercially produced in different countries of the world are described in brief to give the reader a good picture about their scopr and working